PERSPEKTIF HUKUM ISLAM TERHADAP UNDANG-UNDANG NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT - Jamaluddin Jamaluddin; Salma Saharuddin (IAI DDI Polewali Mandar, 2021)
The Birth of Law No. 23/2011 marks a new era of transformation of the national charity which has given rise to a new paradigm of charity management in our country. Some rules are the result of constitutive ijtihadin the ﬁeld of charity gets a reaction from some quarters, especially related to the management of charity by the state authority. Regardless of the debate which led to the material and formal lawsuit, there are several key issues to be further analyzed in relation to the reconstruction of ﬁqh paradigm evaluated from the perspective of contemporary Islamic law. First, the authorities and the involvement of the state as charities through the agency or institution that is ofﬁcially established or recognized by the state, so that the management of charity can be done effectively, guaranteed. And have legal certainty. Secondly, the absence of sanctions for muzaki who shirk the obligation of charity in Law No.23 / 2011 shows that the payment of charity is voluntary, therefore charity regulations in Indonesia are still considered weak in the legal framework that can bind to the individual or business entity that is exposed to the taxpayer , Third, the reform paradigm of subject, object and charity tasarruf ﬁeld have already accommodated in Law No.23 / 2011 in accordance with the principle of maslahatand justice. Fourth, the relationship of charity and tax reafﬁrmed in the amendment of new Law charity as ﬁscal incentives for charity payers to make charity as a reduction of PKP (tax deduction), although this provision has not been able to realize the position of charitywhich is more signiﬁcant as a tax deduction (tax credit).